Sanad-Based Learning and Teaching Resources: Relevance, Implementation, and Challenges in Contemporary Islamic Education - Fakhrullah Fakhrullah; Rustam Ibrahim (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although learning resources in the digital era have received considerable attention, research specifically addressing the integration of modern learning resources with the traditional sanad-based learning system in Islamic education remains limited. This study aims to analyze the concept of learning resources from the perspective of Islamic education, explain the nature and urgency of sanad-based learning, and formulate strategies for integrating modern learning resources with Islamic scholarly traditions. A qualitative approach with a library research design was employed, using relevant literature selected through a purposive literature selection strategy. Data were collected through documentation of textual sources and analyzed using content analysis. The findings indicate that learning resources in Islamic education are holistic, encompassing revelational (naqli), rational-empirical (‘aqli and tajribi), and spiritual (irfani) dimensions. Within this framework, teachers serve as central authorities through sanad, which functions as a quality assurance mechanism that ensures the validity, authority, and spiritual value of knowledge. These findings contribute to the development of Islamic educational methodology and extend current understanding of contemporary sanad-based learning platforms and curricula. The study concludes that synergy between modern learning resources and the sanad tradition is essential for maintaining the quality, authenticity, and sustainability of Islamic education in the digital era. The implications include theoretical contributions to Islamic pedagogy and practical guidance for Islamic educational institutions in implementing sanad digitalization, curriculum integration, and adaptive learning platforms. This study also opens opportunities for further empirical research on the challenges of verifying digital sanad authority.